KOMUNIKASI ORGANISASI DALAM DUNIA KERJA DIGITAL: SEBUAH REVIEW LITERATUR SISTEMATIS - Ahmad Akbar Zaini; Keisha Miranda Panjaitan; Nurul Aini Rosyida (Jurnal Komunikasi, 2026)
The development of digital technology has transformed organizational communication from conventional face-to-face interaction to online platform-based communication, along with the increasing adoption of remote and hybrid work in the post-COVID-19 era. This study aims to identify the transformation of organizational communication in the digital workplace and analyze its challenges and implications for communication effectiveness. The method used is a systematic literature review of peer-reviewed articles from Scopus and Google Scholar published between 2019 and 2026, using the keywords “organizational communication” and “digital workplace.” The selection process involved identification, screening, and eligibility stages based on inclusion and exclusion criteria. Thematic analysis was conducted through coding and categorization to identify key patterns. The findings show that organizational communication has become more multidirectional and technology-driven, improving efficiency while introducing challenges such as limited non-verbal cues, information overload, and digital literacy gaps. Digital leadership plays a crucial role in fostering trust and communication effectiveness. This study concludes that digital organizational communication is a multidimensional phenomenon requiring an integrated technological, social, and psychological approach.